Academic Grieving: (Critical) Reflections on the Dangers of Romanticizing DEI in Engineering Education - James Holly Jr.; Amy Slaton (Studies in Engineering Education)
The following editorial shares a perspective on a contemporary issue that we are aware can be considered controversial. As active members of the engineering education research community we welcome open dialogue concerning our position; that is why we chose this venue because of its explicit mechanism enabling such discourse. We understand the potential of our urgent tone to be perceived as critical, even perhaps hurtful, though we write assertively in order to describe entities and circumstances we consider having already caused tremendous hurt. Our intent is to provide a sobering perspective to our comrades who have invested significant time and energy in working toward diversity, equity, and inclusion (DEI) over the past few decades, an investment we see ourselves as having made. We seek not to chastise, instead realizing that as knowledge producers we have a responsibility to engage with knowledge already produced, and with the practices that have resulted. The serious flaws that critical DEI scholars have already delineated should not be dismissed because the pain is widespread now. As an engineering education researcher (James) and a historian of engineering (Amy), we each have a demonstrated record of personal and professional efforts to appreciate various forms of diversity, enact equity, and broaden inclusion, including but not limited to: leadership within ASEE’s Liberal Education/Engineering & Society Division; co-founding the Equity, Culture, and Social Justice Division; authoring a book characterizing the disenfranchisement of engineering education within Historically Black Colleges/Universities; and facilitating after-school enrichment programs in low-wealth communities, to name a few. Additionally, James is an untenured faculty member, though positioned at a well-resourced and highly regarded institution, whose federal Faculty Early Career Development Program (CAREER) grant was recently terminated. We are not unscathed, though we suspect the norms of conflict evasion in engineering could cause the tone of the message to be used as a scapegoat for the discomfort it may provoke (Tonn & Hira 2024). At the same time, we know that conditions of institutional employment and occupational security can constrain our conduct. Thus, many within the engineering education community who are decrying recent political actions regarding DEI have caused harm themselves or neglected the harm caused prior to and during the growth of DEI initiatives in recent years (Dietz et al. 2023; Feinstein et al. 2025; Holly & Coley 2023). Therefore, following recent conversations with our friends and colleagues we center the perspectives and reflect the tone of those whose viewpoints remain outside the mainstream discourse.